An Introduction to Waste Management and Circular Economy - van Ewijk, Stijn (UCL Press, 2023)
This introductory textbook provides an essential interdisciplinary guide to waste management and circular economy. It helps students to understand the drivers of waste, the environmental, social, and economic impacts of waste generation, and best practices and technologies for waste management, recycling, energy recovery and disposal. With helpful, full-colour diagrams throughout, each chapter includes learning objectives, introduction to concepts and themes, exercises and review sections, to guide students through the book. The textbook is ideal for teaching environmental engineering and science, as well as interdisciplinary environmental programmes. Praise for An Introduction to Waste Management and Circular Economy 'This textbook is a key resource for those studying and working in the waste & resource management sector. Improving waste management has potential to significantly reduce GHG emissions and its impact on the climate crisis. The accessible, student-focused approach within this book makes a valuable contribution to understanding this area and I strongly recommend it.' Phil Longhurst, Professor of Environment and Energy Technology, Cranfield University. 'Waste management and the circular economy are incredibly complex issues, but this textbook breaks them down into easy-to-understand sections, whatever your level of expertise. The use of exercises, illustrations, and examples together with the clarity of the writing mean that you can go from novice to knowledgeable in one book. All the key factors such as material lifecycles, legislation and practice are considered, making this a comprehensive guide to everything you need to know about this topic and what we need to do to help save our planet.' Professor Margaret Bates, visiting Professor of Sustainable Wastes Management University of Northampton and past President of CIWM. 'This new textbook offers readers a comprehensive guide of how to transform waste into resources through the circular economy. I highly recommend for students learning about best practices in waste management and energy recovery.' Ming Xu, Professor of Environmental Ecology, Tsinghua University